THE EFFECT OF FERMENTED DRAGON FRUIT (Hylocereus polyrhizus) SKIN POWDER TO THE INTERNAL AND EXTERNAL QUALITIES OF LOHMANN BROWN CHICKEN AT THE AGE 18-22 WEEKS - A., Kurniawan; Dewi, G. A. M. K.; Wiyana, I K. A. (Jurnal Peternakan Tropika, 2019)
The study aimed to determine the effect of fermented dragon fruit skin powder ( Hylocereus polyrhizus ) in rations on the external and internal qualities of Lohmann Brown chicken eggs age of 18-22 weeks at the research station of the Animal Husbandry Faculty, Udayana University, Jimbaran, Badung, Bali. The study was conducted for 5 weeks. The design used was Completely Randomized Design (CRD) with three treatments and five replications. Each replication consisted of 3 chickens so that the total chickens used were 45 chikens. The treatment was ration with out fermented dragon fruit skin ration as a control (R0), ration with fermented 5% (R1) dragon fruit peel flour, and commercial ration (R2). The variables observed were egg weight, shape index, shell thickness, shell weight, yolk color,pH and Haugh unit . The result showed that an increase in egg weight, eshell weight, and yolk color in treatments R1 and R2 significantly different (P <0.05), to treatment R0. Compared to in contrast to egg shape index, shell thickness, pH and Haugh Unit . Based on the results of the study, it can be concluded that the use of 5% fermented dragon fruit skin powder ( Hylocereus polyrhizus ) in Lohmann Brown chicken can improve external qualities such as egg weight, and internal quality such as eggshell weight, and egg yolk color, and not influences on external quality such as egg shape index, and internal quality such as egg shell thickness, Haugh unit , and egg pH in Lohmann Brown chickens aged 18-22 weeks.   Keywords: Lohmann Brown, dragon fruit skin flour, commercial ration, egg quality